The Rise of the Nation-State across the World: Understanding the Rise of Nation-States: Examining Modernization, Power Shifts, and Global Political Dynamics (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Why, during the last two centuries, have nation-states spread over the globe, supplanting earlierforms of political organization like empires, kingdoms, and city-states? We put major parts ofmodernization, global polity, and historical institutionalist ideas to the test using a new dataset includinginformation on 145 of today's nations from 1816 until the year they gained nation-statehood. According tohistorical analyses, the emergence of a nation-state is more probable when a change in power offersnationalists the opportunity to either topple or absorb the existing authority. Power shifts towardnationalists as nation-states proliferate inside an empire or among neighbors. Industrialization, thespread of literacy, and the rise of authoritarian government—all hallmarks of the modernization theoriesof Gellner, Anderson, Tilly, and Hechter—are not borne out by the data. Nor, according to Meyer's worldpolity theory, is the increasing dominance of the nation-state model a reliable indicator of specificinstances of nation-state creation. Rather from domestic or global structural forces operating over thelong duree, we argue that the growth of the nation-state across the world is driven by proximal andcontextual political dynamics placed at the local and regional levels.